EFFECT OF DIFFERENT ACIDITY CONDITIONS ON THE STRUCTURAL PROPERTIES OF ZIRCONIA CERAMICS - Machado, Luciane Massaroto Gonçalves; Vilanova, Bruno Parreira de Oliveira; Zanatta, Lívia Pelzl Bittencourt; de Moraes, Iasmim Gabrielly Campos; Barbieri, Milena Cristina Miranda; Rezende, Leticia Yara Zanzin; Sachs, Rudinei; de Andrade, José Rubens Santos; Mello, Luis Fernando Gamboni; Teixeira, Itamar Francisco; Prado, Fabiola Stahlke; González, Alejandra Hortencia Miranda (Seven Editora, 2024)
In this study, two groups of dental ceramics exposed to acidic conditions were evaluated: Group 5Y-TZP (Zirconia stabilized by 5mol% Y2O3 and obtained experimentally by chemical synthesis), and Ceramill® Zirconia Group, commercially acquired. Both materials were compacted in the form of pellets, using a mold with a diameter of 6 mm and a hydraulic press, applying a uniaxial load of 3 tons for 60 seconds. After the pressing stage, the pellets were sintered at 1500ºC for 2 hours. All the tablets produced (N=30) were weighed on an analytical scale and then divided according to the acid immersion solutions into 4 media: SA (artificial saliva), SL (orange juice), CC (cola [Coca-Cola] and C (coffee). The tablets were stored in an oven at 37ºC for 72 hours and after the end of this time they were washed in water and dried on absorbent paper. Their masses were again measured in order to evaluate the possible loss of mass during storage. The effect of the acid medium on the crystallinity of the ceramics was evaluated by X-ray diffraction (XRD) analysis, while the chemical bonds were evaluated by Infrared Vibrational Spectroscopy (FTIR). The XRD analyses indicated that, regardless of the acidic medium, none of the ceramic groups observed a change in the crystallinity pattern. The FTIR spectra indicated the presence of new absorption bands, possibly due to the permeability of the acid solutions on the surface of the ceramic samples. DOI:https://doi.org/10.56238/sevened2024.037-028